A Temporal and Spectral Analysis System Design, to Detect Vibration Failures in Electrical Motors - Moreno-García, Francisco Ernesto; Becerra-Vargas, José Armando; Rendón-Echeverri, Carlos Andrés (Universidad Pedagógica y Tecnológica de Colombia, 2014)
This document is based on the experimental development of a measurement and analysis vibrations system, to provide a study of the most relevant variables used in the spectral analysis of electric motors, in order to detect possible faults. This analysis system was implemented in a test bank developed by The Research Group in Automation and Control (GIAC) of the University Francisco de Paula Santander.